Tranzityvinių sangrąžinių veiksmažodžių sinonimai - Geniušienė, Ema (Kalbotyra, 1981)
This paper concerns itself with the principal semantic classes of Lithuanian transitive reflexive verbs (the marker is the reflexive affix -si-) and their synonymy with the following constructions: a) non-reflexive verbs and the dative reflexive pronoun sau: Petras pirkosi mašiną = Petras pirko sau mašiną = “Peter bought himself a car”; b) non-reflexive verbs with an object defined by the possessive pronoun savo: Petras prausiasi veidą = Petras prausia savo veidą = “Peter washes his face”; c) non-reflexive verbs: Petras prausiasi veidą = Petras prausia veidą = “Peter washes his face”.Each semantic class of transitive reflexive verbs possesses a particular set of synonyms, six synonymic sets being distinguished (the seventh set consists of reflexives alone). In nearly all the sets the transitive reflexive verbs are the most commonly used in speech, their synonyms being either rarely used for some particular purposes or not occurring at all. The distribution and interchangeability of the transitive reflexives and their synonyms in typical environments are discussed in detail.